2022
DOI: 10.1136/gutjnl-2022-328389
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota influence anastomotic healing in colorectal cancer surgery through modulation of mucosal proinflammatory cytokines

Abstract: ObjectiveColorectal cancer (CRC) is the third most diagnosed cancer, and requires surgical resection and reconnection, or anastomosis, of the remaining bowel to re-establish intestinal continuity. Anastomotic leak (AL) is a major complication that increases mortality and cancer recurrence. Our objective is to assess the causal role of gut microbiota in anastomotic healing.DesignThe causal role of gut microbiota was assessed in a murine AL model receiving faecal microbiota transplantation (FMT) from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…Subclinical inflammation is increasingly recognised as a potential driver of poor anastomotic healing in bowel surgery. In keeping with our findings,1 a recent report showed that preoperative levels of circulating white cells were higher in patients that developed AL after colorectal surgery 6. Another study suggested that serum chemokine levels were higher before surgery in patients experiencing AL,7 and more evidence has emerged on the impact of preoperative low-grade inflammation on AL in gastric and oesophageal surgery 8 9.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Subclinical inflammation is increasingly recognised as a potential driver of poor anastomotic healing in bowel surgery. In keeping with our findings,1 a recent report showed that preoperative levels of circulating white cells were higher in patients that developed AL after colorectal surgery 6. Another study suggested that serum chemokine levels were higher before surgery in patients experiencing AL,7 and more evidence has emerged on the impact of preoperative low-grade inflammation on AL in gastric and oesophageal surgery 8 9.…”
supporting
confidence: 91%
“…Colonic mucosal biopsies were collected during surgery from all patients and the levels of nine cytokines were measured (online supplemental material), confirming higher levels of MIP-1α, MIP-2, MCP-1 and IL-17A/F in patients who later developed AL (figure 1A). This larger cohort also revealed that the basal levels of IL-1β and tumour necrosis factor alpha, which we have previously shown to be increased after surgery in patients with AL,1 were already high before completion of the anastomosis. Proinflammatory IL-5 and interferon-gamma were also increased at baseline.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…The study by Hajjar et al provides further evidence that the microbiome represents a critical missing piece in this puzzle because it modulates the innate immune response to anastomotic wound healing 2. The more intriguing observation from this work is that it is possible to transfer a colonic healing phenotype through the transplantation of preoperative faecal samples and even individual bacterial strains.…”
mentioning
confidence: 69%